Pengembangan Sistem Informasi Donor Darah Terintegrasi untuk Monitoring Stok Darah pada Rumah Sakit - Ammar Kamil Al Abror; Yunanda Rizki Sitompul; Calvin Sahputra Buulolo; Debi Yandra Niska (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The absence of integrated blood stock management in hospitals, relying on current manual procedures, frequently results in delayed services and challenges in fulfilling blood requirements under emergencies. This research seeks to design and build a web-based blood stock monitoring platform called HemoBridge, offering real-time data accessible by the public, healthcare facilities, and the Ministry of Health. The System Development Life Cycle (SDLC) framework with the well-known Waterfall approach was adopted, encompassing needs analysis, system architecture, development, verification, deployment, and upkeep. This study used a qualitative methodology through field observation and literature review. The platform was developed using PHP and the Laravel framework, with HTML, CSS, JavaScript, and MySQL as supporting technologies. Findings indicate HemoBridge was successfully deployed with core features comprising a comprehensive landing page, donor education, role-based access control, an integrated hospital management panel, a Ministry of Health dashboard, and an advanced blood stock search module with referral capability. Validation through Black Box Testing across six primary functions confirmed all features performed as intended. The platform demonstrates the capacity to enhance data management efficiency, accelerate information retrieval, and strengthen evidence-based decision-making in healthcare. Prospective enhancements include automated stock alerts, data encryption, and wider interoperability with health institutions throughout Indonesia.